Performance Management Based on Culture: Key to Developing Dynamic Capabilities in the Creative Industry through Technology and Community Participation - Agustian, Kresnawidiansyah; Subari; Wiwin; Zen, Agustian (PT. LITERASI SAINS NUSANTARA, 2024)
The creative industry in Indonesia plays a vital role in the economy as a source of income, job creation, and innovation driver. However, this industry also faces significant challenges, including rapid market changes, intense competition, and the need for continuous innovation. This research will review various studies and literature discussing culture-based performance management, dynamic capabilities, technology, and community participation in the context of the creative industry. Our main focus is to identify best practices and challenges faced and provide strategic recommendations for effective implementation. The research method uses a literature review approach with a qualitative method. The data used in this study is obtained from Google Scholar with a publication range between 2009 and 2024. The results show that culture-based performance management, dynamic capabilities, technology, and community participation play an important role in the development of the creative industry in Indonesia. The application of local cultural values in performance management can enhance company identity, employee motivation, and relationships with consumers. Dynamic capabilities enable companies to adapt quickly to market changes, while technology provides tools for efficiency and performance monitoring.